THE STUDY OF THE HIGH-RISE BUILDINGS FACE - Tantarto Sugiman; Uras Siahaan; Rumiati Rosaline Tobing (International Journal on Livable Space, 2017)
One of the indicators that reflects the city's development is the rapid growth of high-rise buildings. The high price and limited available land coupled with the growth and increasingly diverse of human needs become the trigger. This is affected by advances in technology, various available materials as well as sufficient economics factor, making high-rise buildings as one of the development options in major cities around the world. Several factors such as, technology, modernity, and economics dominate the image high-rise buildings. Is it possible to construct the unique high-rise buildings in order to be different from each other? The paper is an initial step in examining the unique concepts that can be applied on high-rise buildings as the products of technology and modernity. The study was conducted through the review of literature in terms of time development in order to seek the unique aspects to be applied on high-rise buildings.  Keywords: high-rise  building, uniqueness, technology, modernity, locality